SIKAP PENGUNJUNG TERHADAP DAYA TARIK WISATA MASJID RAYA SULTAN RIAU DI PULAU PENYENGAT PROVINSI KEPULAUAN RIAU - Iga Safa Marwani; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
With the many visitors coming from different regions that have different attitudes will have an impact on the views on the Masjid Raya Sultan Riau. This is because of an assessment of the object faced by which each person has differences in judgment. This study aims to determine the attitude of visitors to the attraction of Masjid Raya Sultan Riau through cognitive, affective, and conative aspects. This research is a research with descriptive quantitative method with a sample of 100 visitors who come to Masjid Raya Sultan Riau and determined by using accidental sampling technique. The data collected by observation, questionnaire, and documentation. The data measurement technique uses the Likert scale and the analyzed by incorporating it into the attitude attribute categories. The results showed that the attitude of the visitors who came to Masjid Raya Sultan Riau included in the category of positive attitude. Keywords : attitude, Masjid Raya Sultan Riau, tourist